The capillary fragility in subjects at sea level, chronic and acute anoxia anoxia - Alhalel Gabay, Benjamin (1951)
The study of capillary blood is why many years of countless jobs, all oriented towards the investigation of its anatomical and histiológica constitution, their physiological responses and pharmacodynamic observable pathological and clinical manifestations.